Evolutions in bread : artisan pan breads and dutch-oven loaves at home - Forkish, Ken (Ten Speed Press, 2022)
"Approachable for the home baker, while still being chock-full of expert knowledge and all-new recipes, Evolutions in Bread covers same-day loaves, overnight cold-proof doughs, and classic levains. Forkish shares the secrets he has learned for making sourdough starter that's more flour efficient, while also exploring classic breads and enriched doughs, such as Japanese milk bread and brioche. Included with each recipe is a handy baking schedule"--Page 2 of cover.